ANALISIS SWOT SEBAGAI STRATEGI MENINGKATKAN DAYA SAING PADA BISNIS USAHA SEPATU (KASUS TOKO SEPATU STARS CABANG MARPOYAN PEKANBARU) - CVhintya Armi; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Stars shoes shop at Marpoyan Pekanbaru department are one of trade business that work under Stars International Company in Surabaya. This trade business work in footwear sector or retail business. More rivalry in trade business that make a challenge for this trade business to always get compete and hold out into rivalry business.This research are purpose to know SWOT analysis and strategy for increase competitiveness along with assembling SWOT analysis. This research are description method with kind of the study research example and data collection are doing by interview and give questioner to some people that include in this research.From SWOT analysis, we know that score of IFAS is 2,84 and score of EFAS is 2,97. It means that if this score are in SWOT diagram, the research indicate that this trade business are in quadrant 1 position. It means that the strongest of this trade business have a circles opportunity and much more power can use to make that opportunity. The higher score for SWOT matric is 4,35 that decide for this trade business. Advisable to apply the SO strategy for defend that trade business to keep on that sector.Keywords : Business Strategy, SWOT (Strength, Weakness, Opportunity, Threat), SWOT Analysis.